Reoperation Rate After Microsurgical Uni- or Bilateral Laminotomy for Lumbar Spinal Stenosis With and Without Low-grade Spondylolisthesis: What do Preoperative Radiographic Parameters Tell Us?. Issue 4 (15th February 2019) - Schär, Ralph T.; Kiebach, Stefanie; Raabe, Andreas; Ulrich, Christian T.
Abstract : Study Design: Retrospective single-center cohort study. Objective: The aim of this study was to analyze the influence of preoperative radiographic parameters on reoperation rates after microsurgical laminotomy for lumbar spinal stenosis (LSS). Summary of Background Data: Decompression for symptomatic LSS has shown to be effective. However, the optimal surgical strategy remains a matter of debate, especially with underlying spondylolisthesis. Methods: Adult patients with LSS who underwent primary laminotomy without fusion between January 2012 and September 2013 at our institution were included for analysis. Disc height (in mm), facet joint (FJ) orientation (degrees), and grade of spondylolisthesis of all surgical index levels (SILs) were analyzed from preoperative magnetic resonance imaging. Patients were contacted in January 2017 by follow-up phone call (mean follow-up 49 months) regarding lumbar reoperation. Results: A total of 161 patients (mean age 68.5 yrs, ±11.3) and 236 SILs were analyzed. Fifty-six patients (34.8%) had low-grade spondylolisthesis involving 60 SILs (25.4%). Twenty-four patients (14.9%) underwent reoperation involving 32 levels. Of latter, 23 SILs (9.7%) had recurrent stenosis (RS) and 9 (3.8%) had adjacent level stenosis. Five patients in total (3.1%) required secondary fusion; all had preexisting spondylolisthesis. SILs with spondylolisthesis had a significantly higher rate of RS requiring reoperation compared with SILs without spondylolisthesis [18.3% (11/60) vs. 6.8% (12/176), P = 0.013]. Disc height and FJ orientation showed no significant difference between patients with and without reoperation, or with and without spondylolisthesis. Conclusion: Decompression alone is reasonable for most patients with LSS and stable low-grade spondylolisthesis. The overall reoperation rate and need for secondary fusion were low in our series. However, patients with spondylolisthesis had a higher rate of reoperation for RS after laminotomy without fusion. This must be taken into account for preoperative risk-benefit analysis, tailored surgical decision making and patient counseling. Level of Evidence: 4 Abstract : Lumbar stenosis with spondylolisthesis had a higher reoperation rate. Yet, overall only 1 in 10 patients required reoperation for recurrent stenosis after laminotomy and the secondary fusion rate was merely 3%. Laminotomy alone is reasonable for most patients with lumbar stenosis, even with stable spondylolisthesis.